Can User-Generated Content Drive the Purchase of Sustainable Products? Exploring the Role of Persuasion Knowledge Among Young Consumers in Jakarta - Agung Stefanus Kembau; Fresi Beatrix Lendo; Antonius Felix; Steffie Debbyana Wijaya (Universitas Bunda Mulia, 2025)
This study explores the significant influence of User-Generated Content (UGC) on the purchase intention for sustainable products among young consumers in Jakarta, Indonesia, with persuasion knowledge acting as a mediating factor. In an era where digital platforms are reshaping consumer behavior, especially in emerging markets, understanding the role of UGC in driving sustainable consumption is essential. While UGC's impact on general consumer behavior is well-documented, its specific effect on sustainability-driven decisions remains underexplored. This study addresses this gap by examining how young, digitally-engaged consumers interpret UGC and how their awareness of persuasive intent shapes their willingness to purchase sustainable products. Employing a quantitative approach, data was collected from 158 respondents in Jakarta, revealing that UGC significantly enhances purchase intention, with persuasion knowledge amplifying this effect. The findings underscore the pivotal role of digital content in fostering sustainable consumption and provide valuable insights for marketers looking to leverage UGC in promoting environmentally-conscious consumer behavior in Indonesia’s rapidly evolving digital ecosystem.